Reduction of Losses in Positioned Electric Drive with Non-Contact D.C. Engine - G. I. Gulkov; A. G. Gulkov; R. Shaibi (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
The paper reveals expediency to substitute a triangle diagram by a trapezoidal one in the case when angular displacements φ ≤ωmax²/ε  are treated by an electric drive. Such substitution makes it possible to reduce heating losses of electric power in an engine at insignificant increase of displacement time.